2019
DOI: 10.1007/s10113-019-01564-x
|View full text |Cite
|
Sign up to set email alerts
|

Runoff dynamics of the upper Selenge basin, a major water source for Lake Baikal, under a warming climate

Abstract: The Selenge basin contributes approximately 50% of the total inflow into Lake Baikal and is thus of high significance for the regional hydrological regime. Our study was conducted in the upper reaches of the basin, where the Selenge river and its tributaries flow through the Mongolian forest-steppe. Monthly and maximum runoff, precipitation, and air temperature data from 12 gauging stations collected between 1978 and 2015 were analyzed to characterize the hydrological regime response to climate change. Concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Rising temperatures could encourage evaporation of inflowing waterways before they reach the lake. Historical data from monitoring sites along the Selenga showed a negative correlation between temperature and river runoff (Zorigt et al, 2019). And wildfires can be expected to increase with aridity due to changes in global pressure systems (Safronov, 2020).…”
Section: Climate Changementioning
confidence: 99%
“…Rising temperatures could encourage evaporation of inflowing waterways before they reach the lake. Historical data from monitoring sites along the Selenga showed a negative correlation between temperature and river runoff (Zorigt et al, 2019). And wildfires can be expected to increase with aridity due to changes in global pressure systems (Safronov, 2020).…”
Section: Climate Changementioning
confidence: 99%
“…This is because the meadow vegetation grows rapidly throughout the summer due to the abundance of water, nutrient enrichment, warm temperatures, and species adaptations. However, variations in water flow, both within and between years [32], and the reduced maximum water flow of the main rivers in the Selenge basin in Mongolia could potentially result in the degradation of wetlands and moist habitats [33]. Tserendash and Bilegt [31] reported a decrease in the number of plant species and pasture productivity in the Selenge basin meadows over the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…We examined NDVI fluctuations at two meadow sites adjacent to the Tamir River system every sixth year between 1991 and 2015. Given the noted decrease in runoff in the Selenge basin's main rivers since the mid-1990s [33] and the ongoing rise in livestock numbers, our study sought to test the following hypotheses. Hypothesis (1): Floodplain meadows experienced a decrease in NDVI from 1991 to 2015 due to reduced moisture levels and increased grazing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a lack of quantitative estimates of the particular climatic drivers impacts on abrupt changes in water delivery to Lake Baikal. Some studies showed importance of evaporation in ow decline (Sinyukovich and Chernyshov 2019b;Zorigt et al 2019) but some stress the importance of precipitation (Frolova et al 2017). Furthermore, it is remains unclear what cause evaporation change in BC on a basin scale (Minderlein and Menzel 2014).…”
Section: Introductionmentioning
confidence: 99%